Light-Driven ZnO Brush-Shaped Self-Propelled Micromachines for Nitroaromatic Explosives Decomposition - Ying, Yulong; Pourrahimi, Amir Masoud; Manzanares-Palenzuela, Carmen Lorena; Novotny, Filip; Sofer, Zdenek; Pumera, Martin (Small (Weinheim an der Bergstrasse, Germany), 2020)
Self-propelled micromachines have recently attracted lots of attention for environmental remediation. Developing a large-scale but template-free fabrication of self-propelled rod/tubular micro/nanomotors is very crucial but still challenging. Here, a new strategy based on vertically aligned ZnO arrays is employed for the large-scale and template-free fabrication of self-propelled ZnO-based micromotors with H2 O2 -free light-driven propulsion ability. Brush-shaped ZnO-based micromotors with different diameters and lengths are fully studied, which present a fast response to multicycles UV light on/off switches with different interval times (2/5 s) in pure water and slow directional motion in aqueous hydrogen peroxide solution in the absence of UV light. Light-induced electrophoretic and self-diffusiophoretic effects are responsible for these two different self-motion behaviors under different conditions, respectively. In addition, the pH of the media and the presence of H2 O2 show important effects on the motion behavior and microstructure of the ZnO-based micromotors. Finally, these novel ZnO-based brush-shaped micromotors are demonstrated in a proof-of-concept study on nitroaromatic explosive degradation, i.e., picric acid. This work opens a completely new avenue for the template-free fabrication of brush-shaped light-responsive micromotors on a large scale based on vertically aligned ZnO arrays.
Keywords: micromotors; vertically aligned arrays; light-driven; explosive degradation; ZnO